Abdominal Massage Improves the Symptoms of Irritable Bowel Syndrome by Regulating Mast Cells via the Trypase-PAR2-PKCε Pathway in Rats - Huanan Li; Wei Zhang; Fei Ma; Xiaofan Zhang; Yuyan Wang; Jingui Wang (Pain Research and Management)
Background. Irritable bowel syndrome (IBS) is a clinical disease mainly characterized as a syndrome of abdominal pain and discomfort, which frequently occurs in humans aged 20–50. Abdomen massage is of great medical significance for the health of the human body, including promoting intestinal peristalsis, relieving constipation, and facilitating weight loss. However, its potential benefits in alleviating IBS and the underlying mechanisms remain elusive. Methods. In this study, we established an IBS model in rats to evaluate the effects of abdomen massage. Forty male Sprague Dawley (SD) rats were randomly assigned into 4 groups: the normal (control) group, IBS group, abdominal massage group, and abdominal massage + ketotifen treatment group (n = 10 rats in each group). Abdominal massage was performed once a day for 5 minutes for 14 days. On day 14, the rats were euthanized and the tissues were analyzed by transmission electron microscopy (TEM), immunohistochemistry or immunofluorescence staining, and laser confocal focus to visualize the micromorphology of the intestinal mucosa. The expression of TRPV1 and the release of trypase were determined by RT-qPCR and western blot. Results. We found that compared with the control group, the mast cells in the IBS group were significantly increased and the increased MC was partially decreased by an abdominal massage with or without ketotifen treatment. We also found that TRPV1 was upregulated in the IBS group. Abdominal massage with or without ketotifen treatment could attenuate the upregulation of TRPV1 in IBS. Mechanically, results of IHC and western Blot suggested that abdominal massage reduces the sensitivity of IBS by regulating the trypase-PAR2-PKCε pathway. Conclusion. Overall, our results suggested that abdominal massage produces a beneficial effect in improving the symptoms of IBS through reducing mast cell recruitment and attenuating the trypase-PAR2-PKCε pathway. Ketotifen could promote the effect of abdominal massage on IBS treatment, which can serve as a potential therapeutic strategy for IBS.